A concepção de educação profissional e tecnológica dos Institutos Federais de Educação, Ciência e Tecnologia (IFETs) nos governos Lula e Dilma - Moritz, Jaqueline (2017)
Policies for Professional and Technological Education assume, under the Lula government and follow the Dilma government, a new north based on expansion and reordering. The proposed measures were established as strategies focused on overcoming the years of decadence that the previous government instituted in this modality of education. Among the policies, it is Law No. 11,892 / 2008 that establishes the Federal Institutes of Education, Science and Technology (FIs). From its legal constitution in 2008 through 2016, the quantitative growth of FIs was significant. According to the data available on the website of the MEC in 2009 were 350 campis and, in 2016, the Federal Network already had 618 units, distributed by all Federative Units. FIs are institutions that offer higher education, basic and professional, to offer professional and technological education in the different types of education. Through the expansion of these institutions across the country, the present research aims to analyze the conception of Professional and Technological Education that guides the performance of FIs in Brazil in the Lula and Dilma governments. The research will be based on the analysis of official documents related to the offer of professional and technological education in Brazil and theoretical references that address the categories: State, Social Policies and Professional and Technological Education. The study is based on a theoretical approach that takes into account the historical context, the social transformations and the relations between the subjects.